Tidsåtgång för rundvirkesmottagning på Södra Cell Mörrum - Svensson, Andreas (2015)
This study was made for the round wood transport company MT Transport AB. Time studies were made in order to analyze time consumption on the mill site for timber trucks delivering round wood at the Södra Cell Mörrum mill. The most interesting was to see how much of the time spent at the factory that was waiting time. In three weeks the study was going on and the drivers were clocking it themselves.